Analisis Sistem Pembayaran Klaim Polis Asuransi Beasiswa Dalam Meningkatkan Penjualan pada PT. Asuransi BAJ di Makassar - Hemy Syamsuri (Jurnal Ekonomika, 2013)
The aim of this study was to know the systems of the fee paid claim insurance scholarship committed by PT Asuransi BAJ Corporation Makassar. Method Used in this research was a descriptive analysis which explained about how far the corporation commits a system of the fee paid